Research on a coordinated control strategy of three-phase photovoltaic converters based on a buck–boost DC link - Chen, Zhiyong; Hao, Zhifang; An, Jiakun; Fan, Wenyi; Huang, Yuan; Liu, Qunying (Frontiers in Energy Research, 2024)
The high inductance current ripple and the PV voltage fluctuations limitation at the DC (direct current) -DC link have been the unsolved problems in the photovoltaic systems tied in grid. A control strategy with a current hysteresis loop is proposed to address the issues of high inductance current ripple in photovoltaic systems which can achieve real-time duty cycle regulation. Differing from the conventional mode that uses one switch in the buck–boost DC–DC link, two switches have been designed here to separate the buck and boost modes for the coordinated control, which can achieve a wide PV voltage fluctuations range. Based on the conventional fixed-duty cycle determination method, a real-time duty cycle determination method is proposed by introducing changes in inductance current. In order to improve power conversion efficiency, the incremental conductance method is improved by introducing the steepest gradient descent to quickly achieve the maximum power point tracking. This study experimentally verifies the proposed current hysteresis coordinated control method, effectively suppressing the ripple of the inductor current and expand the PV voltage fluctuation in the DC–DC link on the basis of maintaining power conversion efficiency as much as possible.